Effect of environmental parameters on squamate reptiles in an urban forest fragment in central Amazonia - ALMEIDA-CORRÊA,Thais (2020)
ABSTRACT The increasing urbanization of the Amazonian biome has promoted the creation of several forest fragments surrounded by an urban matrix, but the relationship of animal assemblages to the urban environment, especially in forest fragments, is poorly known. Here we aimed to 1) determine the composition of the squamate fauna of the largest urban forest fragment from central Amazonia, in the Brazilian city of Manaus, and 2) evaluate the influence of environmental parameters on assemblage diversity. We sampled 10 standardized riparian plots through visual search in six surveys between 2008/09 and 2015, totaling 360 observer-hours. We found 15 species of lacertoids (lizards and amphisbaenians) and seven species of snakes through active search. After considering occasional encounters and search in museum collections, we recorded a total of 24 lacertoid and 22 snake species. Multiple regression models indicated that species richness and abundance of individuals increased with the distance from the edge of the fragment, while other structural parameters of the environment did not affect the assemblage. We conclude that this forest fragment 1) consists of a subset of the regional species pool, and 2) undergoes reduction of species richness and abundance of individuals from the center to the borders. This and additional urban forest fragments should be continually monitored in order to evaluate their long-term role in maintaining the tropical biodiversity.